Avaliação da complacência intracraniana como ferramenta complementar ao diagnóstico da fibromialgia e monitoramento terapêutico com aplicação de laser e ultrassom: estudo piloto. - Rodrigues, Tiago Zuccolotto (Universidade Federal de São Carlos, 2025)
Fibromyalgia is a chronic pain syndrome of multifactorial origin, whose pathophysiology is not yet fully understood. Recently, alterations in intracranial compliance (ICC) have been investigated as possible mechanisms associated with the symptoms of this condition. This pilot study aimed to evaluate intracranial compliance as a potential diagnostic marker of fibromyalgia, as well as to analyze the effects of combined laser and ultrasound intervention on physiological variables and clinical outcomes. Sixteen individuals participated in the study, including ten diagnosed with fibromyalgia and six healthy controls. The variables P2/P1 ratio, Time to Peak (TTP), beats per minute (BPM), pain score (VAS), sleep quality assessed by the Pittsburgh Sleep Quality Index, and functional impact measured by the Fibromyalgia Impact Questionnaire (FIQ) were evaluated before and after photobiomodulation combined with ultrasound, applied to the palms of the hands. The results demonstrated that individuals with fibromyalgia presented significantly altered patterns of intracranial compliance, with elevated P2/P1 and TTP values compared to controls. After the intervention, significant improvements in compliance were observed, with reductions in P2/P1, TTP, and BPM values, in addition to marked clinical improvements in pain scores, sleep quality, and functional impact. These findings suggest that intracranial compliance may be considered a potential diagnostic marker for fibromyalgia. Furthermore, the noninvasive laser and ultrasound intervention proved effective in modulating physiological parameters and improving symptoms, contributing to a novel diagnostic and therapeutic approach for the syndrome.
Assessment of intracranial compliance as a complementary tool for the diagnosis of fibromyalgia and therapeutic monitoring with the application of laser and ultrasound: a pilot study
Keywords: Fibromialgia; Pressão intracraniana; Complacência intracraniana; Fotobiomodulação; Ultrassom. Diagnóstico; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar